Effects of cooking and food matrix on estimated mineral bioavailability in Mloukhiya, a Mediterranean dish based on jute leaves and meat. (March 2018) - Njoumi, Sondos; Bellagha, Sihem; Icard-Vernière, Christèle; Picq, Christian; Amiot, Marie Josèphe; Mouquet-Rivier, Claire
Abstract: Traditional Mediterranean plant-based dishes could allow tackling malnutrition while preserving the cultural heritage. To determine the effect of the cooking method on mineral bioavailability, the content in minerals and chelators of Mloukhiya, a Mediterranean dish based on jute leaves ( Corchorus olitorius ) that contains also meat, was monitored during the whole cooking process. Mineral bioaccessibility was assessed by measuring in vitro dialyzability. Model equation was also used to estimate mineral bioavailability. Comparison of Mloukhiya samples collected at different cooking time points showed that the dish total mineral content did not change despite the exchanges between sauce and meat during cooking. However, iron bioavailability decreased, because 58% of heme iron was degraded after 5 h of cooking and non-heme iron showed poor bioaccessibility (1.2%), mainly due to its high content of phenolic compounds. The bioaccessibility of other minerals (zinc, calcium, magnesium and potassium) was high, indicating that the food matrix had no or little effect. The mineral bioavailability values predicted by using mathematical models were of the same order of magnitude as the bioaccessibility values. Graphical abstract: Highlights: High polyphenol content in Mloukhiya was responsible for low iron bioavailability. Zn, Ca, Mg and K bioaccessibilities were not affected by the Mloukhiya matrix. Cooking reduced the polyphenol content but iron bioavailability remained low. Predicted mineral bioavailability and dialyzability were of the same order of magnitude. The Mediterranean Mloukhiya dish was rich in zinc and source of calcium and magnesium.